Increased sporulation underpins adaptation of Clostridium difficile strain 630 to a biologically–relevant faecal environment, with implications for pathogenicity. Issue 1 (December 2018) - Ternan, Nigel; Moore, Nicola; Smyth, Deborah; McDougall, Gordon; Allwood, James; Verrall, Susan; Gill, Christopher; Dooley, James; McMullan, Geoff
Abstract Clostridium difficile virulence is driven primarily by the processes of toxinogenesis and sporulation, however manyin vitro experimental systems for studyingC. difficile physiology have arguably limited relevance to the human colonic environment. We therefore created a more physiologically–relevant model of the colonic milieu to study gut pathogen biology, incorporating human faecal water (FW) into growth media and assessing the physiological effects of this onC. difficile strain 630. We identified a novel set ofC. difficile –derived metabolites in culture supernatants, including hexanoyl– and pentanoyl–amino acid derivatives by LC-MSn . Growth ofC. difficile strain 630 in FW media resulted in increased cell length without altering growth rate and RNA sequencing identified 889 transcripts as differentially expressed (p < 0.001). Significantly, up to 300–fold increases in the expression of sporulation–associated genes were observed in FW media–grown cells, along with reductions in motility and toxin genes' expression. Moreover, the expression of classical stress–response genes did not change, showing thatC. difficile is well–adapted to this faecal milieu. Using our novel approach we have shown that interaction with FW causes fundamental changes inC. difficile biology that will lead to increased disease transmissibility.